2007
DOI: 10.1007/s10964-007-9228-9
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Timing of First Sex and Delinquency

Abstract: The relation between timing of first sex and later delinquency was examined using a genetically informed sample of 534 same-sex twin pairs from the National Longitudinal Study of Adolescent Health, who were assessed at three time points over a 7-year interval. Genetic and environmental differences between families were found to account for the association between earlier age at first sex and increases in delinquency. After controlling for these genetic and environmental confounds using a quasi-experimental des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 61 publications
8
61
1
Order By: Relevance
“…At Waves III and IV, participants were asked whether they had ever had vaginal intercourse and, if so, how old they had been (in years) when they first had sex. As in previous studies using this data set (e.g., Harden, Mendle, Hill, Turkheimer, & Emery, 2008), to minimize telescoping, analyses used the age at first sex from the earliest wave in which the participant reported having had sex. For example, if an adolescent reported having had sex for the first time at age 13 in Wave I and at age 14 in Wave II, the reported age from Wave I was used.…”
Section: Methodsmentioning
confidence: 99%
“…At Waves III and IV, participants were asked whether they had ever had vaginal intercourse and, if so, how old they had been (in years) when they first had sex. As in previous studies using this data set (e.g., Harden, Mendle, Hill, Turkheimer, & Emery, 2008), to minimize telescoping, analyses used the age at first sex from the earliest wave in which the participant reported having had sex. For example, if an adolescent reported having had sex for the first time at age 13 in Wave I and at age 14 in Wave II, the reported age from Wave I was used.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, studies have revealed that between 23% and 36% of the variance in television viewing habits are influenced by genetic factors (Kirzinger, Weber, & Johnson, 2012;Plomin, Corley, DeFries, & Fulker, 1990). Without employing a research design capable of controlling for genetic influences, it remains possible that the associations between daily television viewing and subsequent antisocial behavior and aggressive personality traits could be confounded by unmeasured genetic influences resulting in a spurious association (Bouchard, Lykken, McGue, Segal, & Tellegen, 1990;Harden, Mendle, Hill, Turkheimer, & Emery, 2008; J. R. Harris, 1998;W. Johnson, Turkheimer, Gottesman, & Bouchard, 2009;Pinker, 2002).…”
Section: The Potential Role Of Genetic Influencesmentioning
confidence: 99%
“…Our research adds to a small but growing list of studies on rape and sexual assault that utilize nationally representative data (Armour & Haynie, 2007;Casey, Beadnell, & Lindhorst, 2008;Harden, Mendle, Hill, Turkheimer, & Emery, 2008) to complement research based on small, non-representative samples of either college students or adolescents convicted of or in treatment for sexual offending. The development of logistic regression models for rare events (King & Zeng, 2001) increases confidence in the robustness of results from studies that examine infrequent outcomes and the diversity of measures available in the Add Health data allowed us to extend research on adolescent rape that has traditionally focused exclusively on social psychological variables.…”
Section: Introductionmentioning
confidence: 99%